ESTERIFICAÇÃO E TRANSESTERIFICAÇÃO SIMULTÂNEAS DE ÓLEOS ÁCIDOS UTILIZANDO CARBOXILATOS LAMELARES DE ZINCO COMO CATALISADORES BIFUNCIONAIS - Ramos,Luiz Pereira (2015)
Palm oil containing 40% fatty acids was converted to methyl esters using zinc carboxylates as the esterification/transesterification catalyst. The reaction was optimized using a factorial design in which the effects of the alcohol:fatty acids molar ratio (MRAG) and the catalyst concentration (CAT) were assessed. The best conversion was achieved with CAT at 4 wt% and MRAG at 4:1. However, the solid catalyst presented significant structural changes after use. For instance, laurate anions were replaced by carboxylates of higher molecular mass, leading to the formation of a new catalytically active layered structure. Also, the glycerin obtained as a co-product contained 86 wt% glycerol.